A yellow fever–Zika chimeric virus vaccine candidate protects against Zika infection and congenital malformations in mice - Kum, Dieudonné B. (NPJ Vaccines, 2018)
The recent Zika virus (ZIKV) epidemic in the Americas led to an intense search for therapeutics and vaccines. Here we report the engineering of a chimeric virus vaccine candidate (YF-ZIKprM/E) by replacing the antigenic surface glycoproteins and the capsid anchor of YFV-17D with those of a prototypic Asian lineage ZIKV isolate. By intracellular passaging, a variant with adaptive mutations in the E protein was obtained. Unlike YFV-17D, YF-ZIKprM/E replicates poorly in mosquito cells. Also, YF-ZIKprM/E does not cause disease nor mortality in interferon α/β, and γ receptor KO AG129 mice nor following intracranial inoculation of BALB/c pups. A single dose as low as 1 × 10(2) PFU results, as early as 7 days post vaccination, in seroconversion to neutralizing antibodies and confers full protection in AG129 mice against stringent challenge with a lethal inoculum (10(5) LD(50)) of either homologous or heterologous ZIKV strains. Induction of multi-functional CD4(+) and CD8(+) T cell responses against ZIKV structural and YFV-17D non-structural proteins indicates that cellular immunity may also contribute to protection. Vaccine immunogenicity and protection was confirmed in other mouse strains, including after temporal blockade of interferon-receptors in wild-type mice to facilitate ZIKV replication. Vaccination of wild-type NMRI dams with YF-ZIKprM/E results in complete protection of foetuses against brain infections and malformations following a stringent intraplacental challenge with an epidemic ZIKV strain. The particular characteristic of YF-ZIKprM/E in terms of efficacy and its marked attenuation in mice warrants further exploration as a vaccine candidate.